2020
DOI: 10.1590/0034-7167-2019-0453
|View full text |Cite
|
Sign up to set email alerts
|

The association between knowledge about HIV and risk factors in young Amazon people

Abstract: Objectives: analyze the association between the level of HIV knowledge among young people from Amazonas region, their sociodemographic profile and infection risk factors. Methods: cross-sectional analytical study, which used a structured questionnaire containing questions about sociodemographic, behavioral aspects and HIV knowledge. Data were grouped by sex and underwent ordinal and binary logistic regression analysis. Results: the students had an HIV knowledge deficit, associated with a low educational leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
1
7
0
5
Order By: Relevance
“…En este estudio, hubo un número significativo de jóvenes que nunca se había realizado pruebas rápidas. Las investigaciones muestran que la mayoría de los jóvenes no se hace la prueba de detección de VIH y que, entre los motivos, se destaca el miedo a un posible diagnóstico positivo o no querer saber si se han infectado (23,24) .…”
Section: Discussionunclassified
“…En este estudio, hubo un número significativo de jóvenes que nunca se había realizado pruebas rápidas. Las investigaciones muestran que la mayoría de los jóvenes no se hace la prueba de detección de VIH y que, entre los motivos, se destaca el miedo a un posible diagnóstico positivo o no querer saber si se han infectado (23,24) .…”
Section: Discussionunclassified
“…In this direction, since 2007, the Brazilian Ministry of Health implemented the Health in School Program, in which the sexual and reproductive health education of young students is addressed. However, a study performed among young public high school students in Belém showed a low level of knowledge, risk behaviors toward the virus, and unawareness of the HIV testing and prevention services places [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study suggests a necessity to reinforce even more this policy. In Belém young high school students had a low level of knowledge about HIV and risk behaviors toward the virus, such as the infrequent use of condoms in sexual intercourse and multiple sexual partnerships [ 36 ].…”
Section: Discussionmentioning
confidence: 99%